PELATIHAN DIGITALISASI MATERI SEJARAH LOKAL RIAU MELALUI BUKU DIGITAL BAGI GURU SEJARAH DI KEC. RENGAT KAB. INDRAGIRI HULU - Bunari, Bunari; Hasibuan, Rizki Ananda; Fikri, Yanuar Al; Syhaputra, Muhammad Afrillyan Dwi; Ramona, Nadia; Rafianti, Ria (Unri Conference Series: Community Engagement, 2024)
Currently, the transformation of physical local history material into digital form is becoming an attraction for history learning. Apart from providing new experiences to students, digitalization is also a means of responding to the challenges of globalization where the trend is moving towards paperless teaching materials. One of the solutions offered is to provide training in creating digital books based on flip builder pro which will produce a book display that can be accessed easily and can be downloaded for free by students just by "scanning the QR code and link". This training applies 3 method stages, namely planning, implementation and evaluation. The products produced are not only digital books, but also books that can play videos and other audio-visual content. The content in the digital book can be filled with local historical material in Riau Province, or can be adapted to material at certain meetings. Apart from realizing digitalization in history learning, this is also a concern considering that local history plays an important role in the formation of great nations, and history also plays a role in shaping human existence. This service was carried out in Indragiri Hulu Regency based on an analysis of the minimum needs for providing learning facilities.